2012
DOI: 10.1007/s00122-012-1889-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biometrical approaches for QTL detection in multiple segregating families

Abstract: Detection of QTL in multiple segregating families possesses many advantages over the classical QTL mapping in biparental populations. It has thus become increasingly popular, and different biometrical approaches are available to analyze such data sets. We empirically compared an approach based on linkage mapping methodology with an association mapping approach. To this end, we used a large population of 788 elite maize lines derived from six biparental families genotyped with 857 SNP markers. In addition, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…Although joint-population analysis in our present study only included two populations sharing one common parent, the result clearly showed that much more QTL were detected and the accuracy of QTL localization was increased, with 318/412 QTL and average marker intervals 12.5/9.6 in single-population/joint-population analysis. Obviously, multiple population analysis could extensively improve the result of QTL detection (Blanc et al 2006;Myles et al 2009;Li et al 2011;Steinhoff et al 2011;Liu et al 2012). bins 2.06, 6.06-6.07 and 8.03-8.04, for TL at bins 4.06-4.07, 6.00, 6.04-6.05 and 9.03, for EH at bins 5.00, 5.00-5.01, 6.07, 6.08 and 7.05, for TB at bins 2.04-2.05, 2.05-2.06, 3.06-3.07, 5.05 and 7.04-7.05, for LOV at bins 1.03-1.04, 2.08-2.09, 4.01, 5.02-5.03, 10.06-10.07 and for LL at bins 1.06-1.07, 1.09, 4.00-4.01, 5.01-5.02, 5.08-5.09, 7.03-7.04 and 8.00-8.02.…”
Section: Comparison Of Qtl Detected In the Two Connected Ril Populatimentioning
confidence: 99%
See 1 more Smart Citation
“…Although joint-population analysis in our present study only included two populations sharing one common parent, the result clearly showed that much more QTL were detected and the accuracy of QTL localization was increased, with 318/412 QTL and average marker intervals 12.5/9.6 in single-population/joint-population analysis. Obviously, multiple population analysis could extensively improve the result of QTL detection (Blanc et al 2006;Myles et al 2009;Li et al 2011;Steinhoff et al 2011;Liu et al 2012). bins 2.06, 6.06-6.07 and 8.03-8.04, for TL at bins 4.06-4.07, 6.00, 6.04-6.05 and 9.03, for EH at bins 5.00, 5.00-5.01, 6.07, 6.08 and 7.05, for TB at bins 2.04-2.05, 2.05-2.06, 3.06-3.07, 5.05 and 7.04-7.05, for LOV at bins 1.03-1.04, 2.08-2.09, 4.01, 5.02-5.03, 10.06-10.07 and for LL at bins 1.06-1.07, 1.09, 4.00-4.01, 5.01-5.02, 5.08-5.09, 7.03-7.04 and 8.00-8.02.…”
Section: Comparison Of Qtl Detected In the Two Connected Ril Populatimentioning
confidence: 99%
“…QTL detection for plant traits using connected RIL populations has not been reported in high-oil maize. Also, QTL detection in multiple segregating families has not been adopted, although previous research proved that such methods could increase the power of QTL detection and the accuracy of QTL localization, and provide more robust estimates of QTL effects across different genetic backgrounds (Blanc et al 2006;Myles et al 2009;Li et al 2011;Steinhoff et al 2011;Liu et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Recent family mapping results based on elite maize breeding material have shown that QTL for complex traits such as grain yield and grain moisture could be detected (Blanc et al 2006;Liu et al 2011Liu et al , 2012bSteinhoff et al 2011). Applying a cross-validation approach revealed a relative bias in the estimates of genotypic variance explained by the detected QTL of 10-60 % depending on the trait and the experiment.…”
Section: Predictive Power Of Detected Qtl and Validationmentioning
confidence: 99%
“…Different types of LDLA analyses have been proposed to account for the LD component. The simplest is to consider that parents carrying the same allele at a given marker are IBD (Yu et al 2008;Liu et al 2012) as done in association mapping. Haplotype-based approaches also have been proposed to group parental alleles and tested by simulations (for instance Jansen et al 2003;Bink et al 2012;Leroux et al 2014).…”
mentioning
confidence: 99%